THE LEVEL OF MOTIVATION AND STUDENTS’ ATTITUDE TO STUDY PATHOMORPHOLOGY - Ройко, Н.В.; Филенко, Б.М.; Проскурня, С.А.; Совгиря, С.М. (World of Medicine and Biology, 2017)
Motivation is a key factor in the successful learning of students at all stages of the formation of their professional qualities. The purpose and objectives of the paper was to define the level of students’ motivation to study pathomorphology, their attitude to the means and methods of learning. Students of the Dental and Medical Faculties have been surveyed, using the developed questionnaire that includes questions to determine factors of the outer and inner motivation of students, their attitude to study pathomorphology, meaningfulness of the learning process. The findings of the study have been established that students’ motivation is crucial in the effective study of a student, his/her attitude to the subject and the formation of the personality of the future professional. Consequently, an educator should constantly explain the material and use visual aids to demonstrate on the examples of the importance of pathomorphology in the practical activity of a physician.